Cerbera odollam toxicity: A review. (August 2018) - Menezes, Ritesh G.; Usman, Muhammad Shariq; Hussain, Syed Ather; Madadin, Mohammed; Siddiqi, Tariq Jamal; Fatima, Huda; Ram, Pradhum; Pasha, Syed Bilal; Senthilkumaran, S.; Fatima, Tooba Qadir; Luis, Sushil Allen
Abstract: Cerbera odollam is a plant species of the Apocynaceae family. It is often dubbed the 'suicide tree' due to its strong cardiotoxic effects, which make it a suitable means to attempt suicide. The plant grows in wet areas in South India, Madagascar, and Southeast Asia; and its common names include Pong-Pong and Othalanga . The poison rich part of the plant is the kernel which is present at the core of its fruit. The bioactive toxin in the plant is cerberin, which is a cardiac glycoside of the cardenolide class. Cerberin has a mechanism of action similar to digoxin; hence, Cerbera odollam toxicity manifests similar to acute digoxin poisoning. Ingestion of its kernel causes nausea, vomiting, hyperkalemia, thrombocytopenia, and ECG abnormalities. Exposure to high doses of Cerbera odollam carries the highest risk of mortality. Initial management includes supportive therapy and administration of atropine followed by temporary pacemaker insertion. Administration of digoxin immune Fab may be considered in severe cases, although efficacy is variable and data limited to isolated case reports. Highlights: Cerbera odollam is a cardiotoxic plant of the Apocynaceae family. The common names of this plant include Suicide Tree and Pong-Pong Tree. The poison rich part of the plant is the kernel present at the core of its fruit. The plant bioactive toxin is cerberin, a cardiac glycoside of the cardenolide class.